Serine Protease Mauritanicain from Euphorbia mauritanica and Phorbol-12-myristate-13-acetate Modulate the IL-8 Release in Fibroblasts and HaCaT Keratinocytes - Guenther, Florian; Maus, Deborah; Hedtrich, Sarah; Melzig, Matthias F. (Planta Medica, 2019)
In recent years, skin reactions such as phytophotodermatitis, contact dermatitis, and other inflammatory responses after contact with chemicals from various plants, e.g., Heracleum mantegazzianum or Hippomane mancinella, are one of the hot topics in phytobiology. Occupational skin inflammation after contact with latices of plants from Euphorbiaceae are common among people who work with plants of this family. Activation of protein kinase C by G protein-coupled receptors such as protease-activated receptors is associated with skin inflammation. In this study, we focused on the inflammatory modulation potential of proteases combined with diterpenes on human skin. Because of its role as a proinflammatory cytokine, we concentrated on the release of IL-8 by fibroblasts and keratinocytes. Therefore, primary human dermal fibroblasts and the HaCaT keratinocytes cell line were used as a model. The results indicated that the combination of the protease mauritanicain from Euphorbia mauritanica and phorbol-12-myristate-13-acetate induced a significantly increased IL-8 release in HaCaT keratinocytes compared to single treatments. The obtained results also suggest that mauritanicain has an anti-inflammatory effect on primary human dermal fibroblasts.
Keywords: protease-activated receptor 2; fibroblasts; keratinocytes; skin; inflammation; cytokines; protease; Euphorbiaceae